Pension System – at the End of the Career Ladder - Rostiashvili, Giorgi (Economic and Environmental Studies, 2020)
The paper represents author’s research on efficiency on pension systems and effectiveness of state social care policies from the perspective of stability of life at the end of career ladder. It refers to the topic Work – Labor/Value, where former employees’ rights and the impact on countries’ economies are discussed. The following topics are presented: social state of the former employees in the end of their career, the structure of the pension systems, comparative analysis of different pension system models, the motivators for the state and companies, efficient model/s of pension funds, responsible authorities and beneficiaries of the system, economic and social impact, ethical standard, life-long learning. The idea of research is connected to the ongoing reform of pension system in Georgia. The author finds the topic very popular not only in Georgia, but in Europe as well. The workforce is the main pillar the country’s economy and stability is based on. What does the future look like for us? Management of pension funds are tightly connected to the capital market. As the capital market strategy is being developed in parallel of pension fund scheme, it contains some uncertainty and risk of failure. Though the current system does not meet the requirements of liberal economy and it ought to be changed.